One-Step Synthesis of Antibacterial Coatings by Plasma Electrolytic Oxidation of Aluminum - Santos, Janaina S.; Rodrigues, Andressa; Simon, Anna P.; Ferreira, Carlise H.; Santos, Vidiany A. Q.; Sikora, Mariana S.; Cruz, Nilson C. [UNESP]; Mambrini, Giovanni P.; Trivinho-Strixino, Francisco (Wiley, 2019)
Aluminum oxide films containing small quantities of silver are produced by plasma electrolytic oxidation of aluminum (97%) in different electrolytes aiming the synthesis of bactericidal coatings over aluminum for food packaging applications. Sodium citrate, citric acid, and sodium silicate, containing Ag nanoparticles (Ag-NPs) or Ag+ ions (AgNO3) are tested as electrolyte. The galvanostatic anodization curves are used as diagnostic to evaluate the production of Ag-alumina coatings in a one-step procedure. Citric acid and silicate media provide more stability and reproducibility in coatings production; however, only coatings produced in silicate solution exhibit antimicrobial effect against Bacillus subtilis bacteria. The oxide films are characterized by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). An irregular porous structure and a silver content of 0.1–1.9 wt.% in the oxide coatings are observed.
Keywords: aluminum; antimicrobial coatings; plasma electrolytic oxidation; silver